Students' emotional engagement in lecturers' personal facebook account - Pillai, Padma; Bolong, Jusang; Osman, Mohd. Nizam; Hashim, Norliana (Human Resource Management Academic Research Society, 2021)
Facebook serves as an excellent platform for student-lecturer to connect. The rise in the use of Facebook by academics is expected, given the positive features of Facebook. Past studies have indicated the benefit of using Facebook in teaching and learning. One salient issue concerning Facebook usage in teaching and learning is students’ emotional engagement in lecturers’ personal Facebook accounts. While there have been substantial studies examining how lecturers use Facebook in teaching and learning, the question of the impact of lecturers’ personal Facebook account on students’ emotional engagement has not been examined. This research examined the level of students’ emotional engagement in lecturers’ personal Facebook use for teaching and learning. The study defined the pre-test and post-test difference before testing the hypotheses difference relating to these factors. The quasi-experimental research design was used for this research, and a total of 60 students connect with their lecturers via lecturers’ personal Facebook account. Participants fill out the self-administered questionnaire on week one (pre-test) and week fourteen (post-test) of the semester. The questionnaire contained questions on the perceived breadth of students’ emotional engagement. The results revealed that students’ emotional engagement is significantly different in pre and post-test of lecturer personal Facebook account. This study contributes to the growing body of knowledge on the use of Facebook in teaching and learning by clarifying the association of students’ emotional engagement on Facebook.